Lactonase Specificity Is Key to Quorum Quenching in Pseudomonas aeruginosa - Rémy, Benjamin; Plener, Laure; Decloquement, Philippe; Armstrong, Nicholas; Elias, Mikael; Daudé, David; Chabrière, Éric (Frontiers in Microbiology, 2020)
The human opportunistic pathogen Pseudomonas aeruginosa orchestrates the expression of many genes in a cell density-dependent manner by using quorum sensing (QS). Two acyl-homoserine lactones (AHLs) are involved in QS circuits and contribute to the regulation of virulence factors production, biofilm formation, and antimicrobial sensitivity. Disrupting QS, a strategy referred to as quorum quenching (QQ) can be achieved using exogenous AHL-degrading lactonases. However, the importance of enzyme specificity on quenching efficacy has been poorly investigated. Here, we used two lactonases both targeting the signal molecules N-(3-oxododecanoyl)-L-Homoserine lactone (3-oxo-C12 HSL) and butyryl-homoserine lactone (C4 HSL) albeit with different efficacies on C4 HSL. Interestingly, both lactonases similarly decreased AHL concentrations and comparably impacted the expression of AHL-based QS genes. However, strong variations were observed in Pseudomonas Quinolone Signal (PQS) regulation depending on the lactonase used. Both lactonases were also found to decrease virulence factors production and biofilm formation in vitro, albeit with different efficiencies. Unexpectedly, only the lactonase with lower efficacy on C4 HSL was able to inhibit P. aeruginosa pathogenicity in vivo in an amoeba infection model. Similarly, proteomic analysis revealed large variations in protein levels involved in antibiotic resistance, biofilm formation, virulence and diverse cellular mechanisms depending on the chosen lactonase. This global analysis provides evidences that QQ enzyme specificity has a significant impact on the modulation of QS-associated behavior in P. aeruginosa PA14.